XIX CENTURY ENGLISH ROMANTIC LITERATURE - Qosimova Saida Umidjon qizi; Khamitov Eldorbek Erkin o’g’li (Лучшие интеллектуальные исследования, 2024)
This thesis aims to delve into the essence of Romanticism within 19th-century English literature, exploring its multifaceted nature through the examination of prevalent themes, literary techniques, and the socio-political influences that shaped the movement. The study encompasses a comprehensive analysis of prominent works and authors, shedding light on the profound impact of Romantic ideals on the literary landscape of the time. By dissecting the works of seminal figures such as William Wordsworth, Samuel Taylor Coleridge, Percy Bysshe Shelley, and John Keats, among others, this thesis seeks to unravel the complexities of Romantic literature, highlighting its enduring relevance and contribution to the literary canon.